Penthalaris, a novel recombinant five-Kunitz tissue factor pathway inhibitor (TFPI) from the salivary gland of the tick vector of Lyme disease, Ixodes scapularis - Francischetti, Ivo M B; Mather, Thomas N; Ribeiro, José M C (Thrombosis and haemostasis, 2004)
Tick saliva is a rich source of molecules with antiinflammatory, antihemostatic and immunosupressive properties. In this paper, a novel tick salivary gland cDNA with sequence homology to tissue factor pathway inhibitor (TFPI) and coding for a protein called Penthalaris has been characterized from the Lyme disease vector, Ixodes scapularis. Penthalaris is structurally unique and distinct from TFPI or TFPI-like molecules described so far, including Ixolaris, NAPc2, TFPI-1 and TFPI-2. Penthalaris is a 308-amino-acid protein (35 kDa, pI 8.58) with 12 cysteine bridges and 5 tandem Kunitz domains. Recombinant Penthalaris was expressed in insect cells and shown to inhibit factor VIIa (FVIIa)/tissue factor(TF)-induced factor X (FX) activation with an IC50 of approximately 100 pM. Penthalaris tightly binds both zymogen FX and enzyme FXa (exosite), but not FVIIa, as demonstrated by column gel-filtration chromatography. At high concentrations, Penthalaris attenuates FVIIa/TF-induced chromogenic substrate (S2288) hydrolysis and FIX activation. In the presence of DEGR-FX or DEGR-FXa, but not des-Gla-DEGR-FXa as scaf-folds, tight and stoichiometric inhibition of FVIIa/TF was achieved. In addition, Penthalaris blocks cell surface-mediated FXa generation by monomer (de-encrypted), but not dimer (encrypted) TF in HL-60 cells. Penthalaris may act in concert with Ixolaris and other salivary anti-hemostatics in order to help ticks to successfully feed on blood. Penthalaris is a novel anticoagulant and a tool to study FVIIa/TF-initiated biologic processes.